Perancangan Sistem Informasi Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) Berbasis Website - Meidina Yasmine, Nadira; Indiyah, Fariani Hermin; Salsabila, Ellis (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2024)
The researches conducted in 2021 indicate the challenges faced by teachers in creating Lesson Implementation Plans (RPP) for the 2013 Curriculum, particularly related to a lack of time and the absence of a system that can facilitate these needs. This study aims to address these issues by establishing a system to assist teachers in formulating RPP efficiently. The development approach involves using the ReactJS framework for the front-end and NodeJS for the back-end. Agile methodology is applied as an approach in the SDLC, aligning with the scale of the system being small and subject to periodic changes. The results of the system testing through User Acceptance Testing (UAT), conducted with 15 respondents, show a user acceptance rate of 90%, indicating that the system has a high utility value with a very suitable predicate.